Wound healing potential of Apamarga Ksharodaka (herbal alkaline water made from Achyranthus aspera Linn.) in excision rodent wound model - Garg, Ayush Kumar; Rai, Sachchida Nand; Prajapati, Chandrabhan; Mishra, Shashank Shekhar; Singh, Santosh Kumar; Sen, Binay (Rzeszów University Press, 2025)
Introduction and aim. Wound healing is a biological process that aims to restore tissue integrity and function. Despite medical advances, wound management remains challenging. Traditional medicinal preparations, like Apamarga ksharodaka (AK), offer promising therapeutic potential due to their phytochemical richness. This study evaluated wound healing and antimicrobial activity of AK. This study aimed to validate the traditional claim of AK’s wound healing potential using an excision wound model. Material and methods. An excision wound model was created using 24 male Wistar rats. A positive control group applied 5% w/w povidone-iodine (PI) ointment. Wound contraction (WC), epithelialization period (ET), wound closure day, and histopathology were assessed. Antibacterial activity was evaluated against Escherichia coli, Streptococcus aureus, Pseudomonas aeruginosa, and Acinetobacter baumannii. Results. AK showed slightly better wound healing than PI ointment, with significant results in WC rate, wound closure, and ET. Histopathology revealed normal skin and organ architecture. The minimum MIC was 6.25 mg/ml against Pseudomonas aeruginosa with a maximum inhibition zone of 15 mm. Conclusion. AK is safe and effective for wound healing.
Ethical approval was obtained from the Institutional Animal Ethical Committee (IAEC) of IMS, Banaras Hindu University (Dean/2010-11/173 dated 23/07/2010).
Keywords: antimicrobial activity; Apamarga ksharodaka; excision wound model; phytochemical richness; traditional medicinal plants; wound; wound healing